COVID‐19: A review of therapeutics under investigation. Issue 3 (19th April 2020) - Crosby, James C.; Heimann, Matthew A.; Burleson, Samuel L.; Anzalone, Brendan C.; Swanson, Jonathan F.; Wallace, Douglas W.; Greene, Christopher J.
Abstract: The COVID‐19 outbreak has disrupted global health care networks and caused thousands of deaths and an international economic downturn. Multiple drugs are being used on patients with COVID‐19 based on theoretical and in vitro therapeutic targets. Several of these therapies have been studied, but many have limited evidence behind their use, and clinical trials to evaluate their efficacy are either ongoing or have not yet begun. This review summarizes the existing evidence for medications currently under investigation for treatment of COVID‐19, including remdesivir, chloroquine/hydroxychlorquine, convalescent plasma, lopinavir/ritonavir, IL‐6 inhibitors, corticosteroids, and angiotensin‐converting enzyme inhibitors.